A nonchromatographic process for purification of secretory immunoglobulins from caprine whey. (21st April 2017) - Matlschweiger, Alexander; Himmler, Gottfried; Linhart, Clemens; Harasek, Michael; Hahn, Rainer
Abstract : Secretory immunoglobulins are an important antibody class being primarily responsible for immunoprotection of mucosal surfaces. A simple, non‐chromatographic purification process for secretory immunoglobulins from caprine whey was developed. In the first process step whey was concentrated 30–40‐fold on a 500 kDa membrane, thereby increasing the purity from 3% to 15%. The second step consisted of a fractionated PEG precipitation, in which high molecular weight impurities were removed first and in the second stage the secretory immunoglobulins were precipitated, leaving a majority of the low molecular weight proteins in solution. The re‐dissolved secretory immunoglobulin fraction had a purity of 43% which could then be increased to 72% by diafiltration at a volume exchange factor of 10. Further increase of purity was only possible at the expense of very high buffer consumption. If diafiltration was performed directly after ultrafiltration, followed by precipitation, the yield was higher but purity was only 54%. Overall, filtration performance was characterized by high concentration polarization, therefore process conditions were set to low trans‐membrane pressure and moderate protein concentration. As such purity and to a lesser extent throughput were the major objectives rather than yield, since whey, as a by‐product of the dairy industry, is a cheap raw material of almost unlimited supply. Ultra‐/diafiltration performance was described well by correlations using dimensionless numbers. Compared with a theoretical model (Graetz/Leveque solution) the flux was slightly overestimated. © 2017 American Institute of Chemical Engineers Biotechnol. Prog., 33:642–653, 2017